Damaged but not destroyed : from trauma to triumph - Todd, Michael (Pastor) (WaterBrook, 2023)
"The #1 New York Times bestselling author of Relationship Goals and Crazy Faith wants you to know that no matter how badly you've messed up, no matter what hardship or pain you've experienced, nothing can destroy the priceless, God-given value of your life"--